Methodological proposal for a new approach in the study of the Peruvian electoral process through public opinion surveys - Huamanchumo de la Cuba, Luis (2002)
This paper was developed from the Consumer Behavior Theory to show how voters take his or her political election in the context of the Peruvian Political Campaign. Conjoint Analysis has been introduced in this field of the social science as a new analytical tool. This paper is a start point from which a future research would be presented with real results and pitfall that I had to face and take solutions on the way